Human Well-Being and Insurgencies in Nigeria: An Examination of Boko Haram Sect - Okon, Emmanuel Okokondem; Zhizhi, Able Shibinya (International Journal of Economics, Business and Management Studies, 2017)
Despite Nigeria’s plentiful agricultural resources and oil wealth, poverty is widespread in the country and a local radical Salafist group has transformed into a Salafi-jihadist terrorist sect called Boko Haram. The group’s activities have caught the attention of terrorism watchers at the international level. This paper seeks to know whether the human well-being condition in Nigeria promotes Boko Haram insurgency. The perception of respondents exhibit high rate of illiteracy, unemployment and poverty in Nigeria as accountable for Boko Haram insurgency. As such, the contend is that more effort should be aimed at revitalization of Nigeria’s economy. In that regard, wasteful spending should be reduced by diverting such funds to establish industries where the youths will have gainful employment; People’s living standard will be improved and poverty reduced. Similarly, more Almajiri schools should be established chiefly in Northern States of the country with the view of using it to educate the teeming illiterate youths in the terrain and therefore reducing Boko Haram foot soldiers.